Efficacy and Safety of a Diabetes Specific Formula in Patients with Type 2 Diabetes Mellitus: A Randomized, Open-label, Crossover Study. - Phanachet, Pariya; Hawkinson, Andrea; Tontrakulrat, Nantanat; Pichitchaipitak, Orawan; Sittikho, Nantaporn; Boonpattararaksa, Jariya; Tongchom, Wanabhorn; Taonam, Naphat; Lepananon, Tanarat; Shantavasinkul, Prapimporn Chattranukulchai; Warodomwichit, Daruneewan (Journal of Nutrition Association of Thailand (Online), 2022)
Managing postprandial hyperglycemia is a frequent challenge for individuals with Type 2 diabetes (T2D). There is a paucity of data examining use of a diabetes-specific formula (DSF) versus a matched isocaloric diet and improved PPG. The present study aimed to evaluate the effects of a new DSF compared to a matched macronutrient isocaloric diet on postprandial glucose (PPG), insulin, and safety in patients with T2D. In this randomized, open-label, crossover study, 30 T2D subjects were randomized into one of two groups: group A received the new DSF and group B received the isocaloric diet. After one-week, participants crossed over to the alternative nutrition intervention. Blood samples measured glucose and insulin levels at baseline, 30, 60, and 120 min post-meal. PPG levels and incremental area under the curve (iAUC) for glucose were significantly lower for group A compared to group B (P=0.007). Postprandial insulin levels were lower at 60 and 120 min for group A compared to group B, though not statistically different. The DSF was well tolerated and no serious adverse events were reported. This study demonstrates that use of a DSF is superior to an isocaloric diet in reducing PPG and tend to improving insulin response in T2D patients. These data suggest use of a DSF offers glycemic benefits and should be included as a medical nutrition therapy for patients with Type 2 diabetes.